2021
DOI: 10.3389/fmed.2021.671035
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Treatment Options for Type 1 and Type 2 Caesarean Scar Pregnancy: A Retrospective Case Series Study

Abstract: Background: There is currently no agreement on the optimal management of caesarean scar pregnancy. Caesarean scar pregnancy is currently categorised into two subtypes according to the site of implantation. This may consequently result in the difference in treatment options. However, the comparison of the success rate of each treatment option according to the subtypes has not been fully investigated.Methods: 71 patients who were treated by uterine curettage (D and C), or uterine artery embolization with curetta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Until now, there have been few studies on the treatment of CSP according to its classification. Our previous research shows that hysteroscopy-assisted laparoscopy is safe and effective for type 2 CSP (Qi et al, 2019), which has been confirmed by other similar studies (Wang et al, 2014;Shen et al, 2021). As the gestational sac is implanted on the scar and grows toward the uterine cavity, the risk of type 1 CSP is relatively lower, therefore, we evaluate the treatment of type 1 CSP based on the therapeutic effect and health economics.…”
Section: Discussionsupporting
confidence: 67%
“…Until now, there have been few studies on the treatment of CSP according to its classification. Our previous research shows that hysteroscopy-assisted laparoscopy is safe and effective for type 2 CSP (Qi et al, 2019), which has been confirmed by other similar studies (Wang et al, 2014;Shen et al, 2021). As the gestational sac is implanted on the scar and grows toward the uterine cavity, the risk of type 1 CSP is relatively lower, therefore, we evaluate the treatment of type 1 CSP based on the therapeutic effect and health economics.…”
Section: Discussionsupporting
confidence: 67%
“…For type II a and type III b CSP, operative resection is deemed appropriate. Numerous studies have demonstrated the efficacy of laparoscopic hysterotomy with wedge resection of the previous scar, thus warranting its recommendation [ 27 , 28 ]. In a review study, laparoscopy demonstrated a success rate of 97% with expedited resolution of HCG levels and absence of complications [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that more than a half of all CSPs treated with dilation and curettage (D&C) alone required additional treatment [ 10 , 11 ]. However, in another study, treatment with uterine curettage had a 95% success rate in cases of type I CSP, while this treatment only showed 27% success in cases of type II CSP [ 12 ]. The blood supply characteristics of different types of CSP may be different, resulting in different bleeding risks.…”
Section: Introductionmentioning
confidence: 99%